Crianças à prova da escola: impasses da hereditariedade e a nova pedagogia em Portugal da fronteira entre os séculos XIX e XX - Boto, Carlota [UNESP] (Associação Nacional de História - ANPUH, 2001)
This paper, as the just title indicates, intends to discuss about Portuguese pedagogical contest at the end of the XIXth century and at the beginning of the XXth century. The used documentary sources were magazines specialized in education, directed whether to the parents, or to the teachers. Such periodicals, that were including articles from reputed intellectuals and pedagogists of the epoch, had the objective to discuss the great questions internationally set within the educational area. They were talking a lot, during the New Pedagogy epoch, about the New Education, a tendency that was intending to bring the science development contributions to the educative area, and about the recent investigation practices, already in force in the countries considered as more advanced, more civilized. One of the themes that deserved a great notability within the specialists in that time, was the one that would give to the education the mission to fight, wether the social obstacles, or the limitations coming from the hereditariness. Against the biological and social determinisms, it was the role of the pedagogy to fight them. In such case, the educative act was seen as a social bet, that would be performed by a specific, specialized and necessarily renewed institution. The school, already considered as tradicional, was not up to the obstacles with which the new educators had to face. Then, it was necessary to modify the old method and content conceptions.

Este trabalho pretende discorrer sobre o debate pedagógico em Portugal do final do século XIX e do início do século XX. As fontes documentais utilizadas foram revistas especializadas em educação, dirigidas quer aos pais, quer aos professores. Tais periódicos, que continham artigos de renomados intelectuais e pedagogistas da época, tinham por objeto debater as grandes questões colocadas internacionalmente no campo educacional. Falava-se muito, na altura, da Nova Pedagogia, da Educação Nova, corrente que pretendia trazer para o campo educativo as contribuições do desenvolvimento da ciência e das recentes práticas de investigação já em vigor nos países tidos como mais adiantados, mais civilizados. Um dos temas que mereceram muito destaque entre os especialistas da época era aquele que conferia à educação a missão de combater, quer os impasses do meio, quer as limitações provenientes da hereditariedade. Contra os determinismos biológicos e sociais, cabia, portanto, à Pedagogia lutar. Sendo assim, o ato educativo era percebido, em larga medida, como uma aposta social, que seria empreendida por uma instituição específica, especializada e necessariamente renovada. A escola, já tida por tradicional, não dava conta dos impasses com os quais os novos educadores se defrontariam. Cabia, então, alterar radicalmente velhas concepções de método e de conteúdo.
Keywords: education; childwood; determinism; educação; infância; determinismo